Scaffolding untuk Mengatasi Kesalahan Menyelesaikan Soal Cerita Sistem Persamaan Linear Dua Variabel - Hartati, Yessy Nur (Jurnal Matematika; Vol 6 No 2 (2016), 2016)
The aims of the research is to describe the student’s errors in solving word problem about two variable linear equations system based Field Independence (FI) and Field Dependence (FD) cognitive style and describe the scaffolding used to solve student’s errors in solving word problem about two variable linear equations system based FI and FD cognitive style. This research uses qualitative research methods by giving test n interviewing on the subject of research. Results showed that students with FI cognitive style make errors in solving mathematical model and stating the final answer. Whereas FD cognitive style of students make errors in understanding the problem, making a mathematical model, completing mathematical model and stating the final answer. The scaffolding given to FI cognitive style student includes reviewing. Whereas the scaffolding given to FD cognitive style student include explaining, reviewing and restructuring
Keywords: cognitive style; scaffolding; student’s errors; two variable linear equations system